Detecting Oil Slicks Using SAR Radar Images and the Google Earth Engine Platform - Ali Kourosh Niya; Ali Ashrafi (Nīvār)
Preventing environmental damage from oil spills has always been considered a big challenge for marine communities. In the meantime, the first step in facing this problem is to reveal and identify the pollution as soon as possible in order to control its spread and adverse effects. Traditional methods that are based on field visits are costly and time-consuming due to the need for equipment and manpower. Therefore, the use of methods based on remote sensing technology and satellite images has been significantly developed recently. In this research, the capabilities of Synthetic Aperture Radar-SAR data, Google Earth Engine, and Geographic Information System environment were used in the form of an integrated framework to accelerate the process of identifying oil slicks. Based on the method of this research, first, the area of interest was determined and the SAR data of the Sentinel 1 satellite was selected in the Google Earth Engine environment. In the next step, oil slicks were revealed through filtering. In order to check the accuracy of the method, the results were compared with records of pollution events in the area of study. Comparing the obtained results with oil pollution events in the study area shows the appropriate efficiency of the proposed framework for detecting oil stains.